The Religious Content of the Presidents' Remarks at the National Prayer Breakfast, 1953–2016. Issue 2 (4th May 2017) - Peterson, Jonathan R.
ABSTRACT: Delivered by every president since Eisenhower (and annually since 1961), the presidents' remarks at the National Prayer Breakfast represent the most succinct presidential expressions of religion in the United States over the past seven decades. This descriptive article of the religious content of those remarks explores the ways presidents have talked about God, prayer, faith, and the Bible. Recent presidents are much more likely to mention God, especially in personal ways. The remarks have become less linguistically complex over time. President Obama's remarks contain the most references to God and faith, whereas George W. Bush's contain more references to prayer.